Downregulation of MARC2 Promotes Immune Escape and Is Associated With Immunosuppression of Hepatocellular Carcinoma - Wu, Dehai; Liang, Shuhang; Guo, Hongrui; Zhang, Shugeng; Yang, Guangchao; Yuan, Yubin; Liu, Lianxin (Frontiers in Genetics, 2022)
The N-reductive enzyme system (NRES), composed of MARC1, MARC2, CYB5, and CYB5R, is responsible for the reduction of N-oxygenated compounds and participates in several physiological processes. For example, MARC2 serves as an important prognostic indicator and is downregulated in hepatocellular carcinoma, and the downregulation of MARC2 is critical to the regulation of lipid metabolism and cell cycle progression. However, the role of MARC2 in tumor immune microenvironment modification had not previously been investigated. In this study, we found that downregulation of MARC2 was associated with the differentiation of CD4+T cells into regulatory T cells (Tregs). Furthermore, restoring the expression of MARC2 could increase the expression of HLA-C and B2M via PPARA-related lipid metabolism signaling pathways, which could facilitate tumor antigen presentation to the tumor-infiltrating T cells. Additionally, MARC2 expression negatively correlated with several immune checkpoints. The immune checkpoint burden was generated based on 28 MARC2-related immune checkpoints. Patients with a higher immune checkpoint burden were predicted to have a poorer prognosis and a lower level of activated CD8+ T cells. The results showed that expression of the NRES is a prognostic indicator of hepatocellular carcinoma and MARC2 contributes significantly to predict the prognosis. Finally, loss of MARC2 in HCC patients was found to facilitate immune escape and was associated with immunosuppression.